Statistical Grouping of Countries Based on Fertilizer Consumption - Arunachalam, Rajarathinam (Science and Technology - Recent Updates and Future Prospects Vol. 4, 2024)
Fertilizers are crucial in modern agriculture which provides essential plant nutrients to enhance crop yields. This study investigates fertilizer consumption patterns across 41 countries from 1961 to 2021. Fertilizer consumption data was obtained from the World Bank's World Development Indicators database. The dataset includes fertilizer consumption data for 41 countries from 1961 to 2021. Descriptive statistics reveal substantial variation in average fertilizer use (kg/hectare) and variability between countries. Statistical analyses confirm significant differences in consumption patterns, with fertilizer consumption identified as a major explanatory factor. Cluster analysis further differentiates countries into two groups based on their consumption levels. These findings highlighted the need to consider fertilizer use within a country-specific context. The collected data suggests that fertilizer consumption patterns differ considerably, with some countries exhibiting high average use and others demonstrating lower consumption levels. Further research exploring the underlying factors driving these variations and their impact on crop yields could inform strategies for optimizing fertilizer use and promoting agricultural sustainability.